2016
DOI: 10.2486/indhealth.2015-0108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mop handle height on shoulder muscle activity and perceived exertion during floor mopping using a figure eight method

Abstract: The aim of this study was to investigate effects of mop handle height on electromyographic (EMG) activities of the shoulder muscles and perceived exertion for the shoulder area during floor mopping using a figure eight method. An experimental study with 13 cleaners was conducted using surface EMG and category ratio (CR-10) scale. EMG activity was recorded unilaterally from the upper trapezius, infraspinatus, anterior and middle deltoid muscles. Each subject performed four trials of mopping and each trial consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 35 publications
0
7
0
13
Order By: Relevance
“…However, in examining specific categories of strategies, our analysis revealed that none of the studies met the criteria for a strong level of evidence that a specific strategy reduces physical exposure. We found moderate evidence for changes in mop design, as well as for mop adjustability (Öhrling et al, 2012; Wallius et al, 2016), as a successful strategy for reducing physical exposure. However, moderate evidence for no effect on physical exposure was found in comparisons of alternative types of tools (Table 5).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…However, in examining specific categories of strategies, our analysis revealed that none of the studies met the criteria for a strong level of evidence that a specific strategy reduces physical exposure. We found moderate evidence for changes in mop design, as well as for mop adjustability (Öhrling et al, 2012; Wallius et al, 2016), as a successful strategy for reducing physical exposure. However, moderate evidence for no effect on physical exposure was found in comparisons of alternative types of tools (Table 5).…”
Section: Discussionmentioning
confidence: 77%
“…In staircase mopping, using adjustable handles decreased levels of muscle activities for the right-hand shoulder and for the left-hand wrist as well as the subjective perceptions of exertion in comparison to use of a nonadjustable mop (Öhrling et al, 2012). Similarly, Wallius et al (2016) demonstrated that by adjusting the mop handle, muscle activity levels for the shoulder and subjective exertion ratings for the shoulder area were decreased. These studies provide moderate evidence that the type of mop handle reduces physical exposure.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations